Factors Influencing University Student Decision to Utilize Mobile Banking in Cambodia: An Extension of UTAUT-2 with SERVQUAL and DIT - Homoly, Hong; Norng, Sokha; Bunteng, Long (Jurnal Akuntansi dan Perpajakan, 2024)
Even though mobile banking has become popular in Cambodia, its adoption among university students is still a question. Hence, this study aims to investigate the factors influencing mobile banking adoption among university students in Cambodia. The study extends the Unified Theory of Acceptance and Use of Technology 2 (UTAUT-2) by integrating Service Quality (SERVQUAL) model, and Diffusion of Innovation (DIT) theory to examine factors driving mobile banking adoption. The study uses a questionnaire to collect data from 520 university students. By using structural equation modeling, the study found that compatibility and observability affect intention through performance expectancy and effort expectancy. The study also found that performance expectancy, effort expectancy, hedonic motivation, price value, and habit all had a significant positive effect on the intention to adopt mobile banking. However, social influence and facilitating condition do not have an impact on intention. At the final path, the study found that performance expectancy, responsiveness, tangible, and intention have a positive impact on the students' behavior to use mobile banking.